Treatment of Crohn’s disease with colony-stimulating factors: An overview - Luisa Guidi; Giammarco Mocci; Manuela Marzo; Sergio Rutella (Dove Medical Press, 2008)
Luisa Guidi1, Giammarco Mocci1, Manuela Marzo1, Sergio Rutella21Department of Internal Medicine, Operative Unit of Gastroenterology, and 2Department of Hematology, Laboratory of Immunology, Università Cattolica del Sacro Cuore, Rome, ItalyAbstract: Current treatments for Crohn’s disease are aimed at suppressing excessive immune activation in the bowel walls. However, alternative strategies can be drawn. These involve the augmentation of the innate immune response, in the hypothesis that patients affected with Crohn’s disease are characterized by a relative immunodeficiency, with failure of the defensive barrier to luminal microbes and microbial products, resulting in a chronic inflammatory process sustained by T-cells. Alternatively, therapy could act by enhancing the number or the activity of subpopulations of T regulatory cells, able to reduce T-cell activation. Colony-stimulating factors are substances that could be efficacious in these settings. In fact, besides in vitro and animal studies, some human studies have been conducted in recent years with both granulocyte-macrophage colony-stimulating factor and granulocyte colony-stimulating factor, the results of which are reported here.Keywords: inflammatory bowel disease, Crohn’s disease treatment, G-CSF, GM-CSF